2015
DOI: 10.1103/physreve.91.062138
|View full text |Cite
|
Sign up to set email alerts
|

Equipartitions and a distribution for numbers: A statistical model for Benford's law

Abstract: A statistical model for the fragmentation of a conserved quantity is analyzed, using the principle of maximum entropy and the theory of partitions. Upper and lower bounds for the restricted partitioning problem are derived and applied to the distribution of fragments. The resulting power law directly leads to Benford's law for the first digits of the parts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As already stated, one of the main findings of our research has been about the data range. Indeed to conform with the law, the data set must contain data in which each number 1 through 9 has an equal chance of being the leading digit; there should be equipartition [42,43]. However, this seems paradoxical.…”
Section: Discussionmentioning
confidence: 99%
“…As already stated, one of the main findings of our research has been about the data range. Indeed to conform with the law, the data set must contain data in which each number 1 through 9 has an equal chance of being the leading digit; there should be equipartition [42,43]. However, this seems paradoxical.…”
Section: Discussionmentioning
confidence: 99%
“…If this partition is done so as to maximize the entropy of the partition, we find that the probability of city size t is given by (2), where λ = M/P. See Appendix A for a derivation of this claim that is inspired by a similar derivation by Iafrate, Miller, and Strach [9]. Miller and Nigrini [10] also explore relations between the exponential probability density (2) and Benford's law (1).…”
Section: Introductionmentioning
confidence: 95%
“…Although this is an expected statistical phenomenon [3], the reasons for it are remarkably obscure, and there remain a number of open problems [4]. Benford's Law has since generated significant interest, including treatments that highlight its connections with entropy: Iafrate et al (2015) [5] showed that the Law is derivable from a statistical mechanics treatment, with Don Lemons (2019) [6] extending their treatment to explicitly show the connection with thermodynamics.…”
Section: Introductionmentioning
confidence: 99%